PJMHS 2021
DOI: 10.53350/pjmhs2115103143
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pembrolizumab and Chemotherpay with Radiology Among Patients of Untreated Pd-L1 Positive Metastatic Triple Negative Breast Cancer

Abstract: Objective: The aim of this study is to compare the outcomes of chemotherapy with radiology and use of pembrolizumab among the patients had metastatic triple negative breast cancer and did not receive any treatment yet. Study Design: Comparative/Observational study. Place and Duration: Breast Clinic Ganga Ram Hospital Mazang Road, Lahore. April 2021-Sep 2021 Methods: Total 70 patients of aged 25-75 years were presented in this study. Patients had metastatic triple negative breast cancer and did not receive any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…A recent trial from Pakistan found that injectable pembrolizumab was a helpful and successful monotherapy among individuals with PD-L1positive mTNBC, with fewer negative effects and a greater rate of effectiveness. [14] Similar outcomes have been shown in studies utilising immune checkpoint inhibitors to treat mTNBC. In the KEYNOTE-012 study, pembrolizumab was used to treat 32 patients with mTNBC.…”
Section: Discussionsupporting
confidence: 62%
“…A recent trial from Pakistan found that injectable pembrolizumab was a helpful and successful monotherapy among individuals with PD-L1positive mTNBC, with fewer negative effects and a greater rate of effectiveness. [14] Similar outcomes have been shown in studies utilising immune checkpoint inhibitors to treat mTNBC. In the KEYNOTE-012 study, pembrolizumab was used to treat 32 patients with mTNBC.…”
Section: Discussionsupporting
confidence: 62%